La concezione dell’eroe nel Rinaldo di Torquato Tasso - Prosenc, Irena (Verbum – Analecta Neolatina, 2019)
This paper aims to show that the place of enunciation influences the production of utterances about the discursive construction of events happening in another society. We take the example of two Belgian writers, Simon Leys and Charles Paron, who lived in Hong Kong and Beijing respectively during the Chinese Cultural Revolution (1966–1976). The places where they lived induced original analyses and isolated them from their social fields, even beyond their ideological positions. We first study their relationship with both the Chinese Cultural Revolution and the discursive productions about it in Europe, and what drove them to write in forms that were unusual to them. We then analyze the conditions of construction of the representations of the revolution.